2015
DOI: 10.1039/c5cc01618e
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting anthracene photodimerization within peptides: light induced sequence-selective DNA binding

Abstract: The unprecedented use of anthracene photodimerization within a protein or peptide system is explored through its incorporation into a DNA-binding peptide, derived from the GCN4 transcription factor. This study demonstrates an effective and dynamic interplay between a photoreaction and a peptide-DNA assembly, with each process able to exert control over the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Starting with the pioneering work by Kim, 54,61 several synthetic strategies have been developed for the dimerization of bZIP peptides, 55,62-64 including disulfide bonding, 54 metal coordination, 65-68 and crosslinking with metal-tunable 69 or photo-switchable linkers. 70-72 These studies have collectively shown the importance of the dimeric organization of the basic domains as well as their proper orientation for DNA binding and recognition. The HCM-based approach that we have described here is complementary to these previously described strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Starting with the pioneering work by Kim, 54,61 several synthetic strategies have been developed for the dimerization of bZIP peptides, 55,62-64 including disulfide bonding, 54 metal coordination, 65-68 and crosslinking with metal-tunable 69 or photo-switchable linkers. 70-72 These studies have collectively shown the importance of the dimeric organization of the basic domains as well as their proper orientation for DNA binding and recognition. The HCM-based approach that we have described here is complementary to these previously described strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Visible light irradiation leads to efficient configurational transformation into cis-isomer. A photostationary state containing 61.1% of cis-isomer was obtained after being irradiated for about 1.5 h. In addition, cis-isomer of PAH-8 is stable at room temperature whereas it almost completely transforms into trans-isomer by heating for 1 h at 120 ℃ in DMSO-d 6 . Similar results were observed after UV light irradiation ( Figure S10), but only the 30.6% of cis-isomer was obtained after being irradiated by UV for about 8 h ( Figure S11), and the cis-isomer of PAH-8 could not transform into transisomer by heating.…”
Section: Photo-responsive Properties Of Organogelmentioning
confidence: 99%
“…Low molecular mass organogelators (LMOGs) can self-assemble through specific noncovalent interactions such as hydrogen bonding, π-π interaction, hydrophobic interaction or Van der Waals force to form diverse nano/micro-structures such as fibers, particles, tubes, and helical ribbons. [1][2][3] Recently, numerous efforts have been devoted to the development of stimuli-responsive organogels, whose properties can be either switched on-off or tuned in the presence of an external or internal chemical or physical stimulus such as light, [4][5][6][7] thermal treating, [8] ultrasound, [9] anion. [10] Among the stimuli-responsive organogels, photo-responsive organogels have attracted considerable attention because light is a non-contaminating stimulus that provides a broad range of tunable parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Structure and design of metal-involved supramolecular architectures based on crystal engineering are currently of interest in the field of supramolecular chemistry and coordination chemistry. [1][2][3][4] The increasing interest in this field is justified not only by their valuable unit structure, but also their potential applications in luminescence, catalysis and biochemistry, [5][6][7][8][9] particularly in modern medicinal chemistry. [6,[10][11][12][13] Among the series of compounds fabricated, the functional complexes attract great attention due to the potential drug value applications.…”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular weak interactions, such as hydrogen bonds, and intermolecular interactions play important roles in the construction of the complexes. The interaction of these complexes with fish sperm DNA (FS-DNA) was monitored and binding constants were determined using UV-visible spectroscopy, which revealed their ability to bind to FS-DNA, with binding constants for the two complexes of 1.88 × 10 4 M −1 (1) and 1.06 × 10 4 M −1 (2). Viscosity experiments further demonstrated the binding of the complexes to DNA.…”
mentioning
confidence: 99%